An in-depth multiphasic analysis of the chocolate production chain, from bean to bar, demonstrates the superiority of Saccharomyces cerevisiae over Hanseniaspora opuntiae as functional starter culture during cocoa fermentation. (February 2023) - Díaz-Muñoz, Cristian; Van de Voorde, Dario; Tuenter, Emmy; Lemarcq, Valérie; Van de Walle, Davy; Soares Maio, José Pedro; Mencía, Alejandra; Hernandez, Carlos Eduardo; Comasio, Andrea; Sioriki, Eleni; Weckx, Stefan; Pieters, Luc; et al.
Abstract: Hanseniaspora opuntiae is a commonly found yeast species in naturally fermenting cocoa pulp-bean mass, which needed in-depth investigation. The present study aimed at examining effects of the cocoa isolate H. opuntiae IMDO 040108 as part of three different starter culture mixtures compared with spontaneous fermentation, regarding microbial community, substrate consumption, and metabolite production dynamics, including volatile organic compound (VOC) and phytochemical compositions, as well as compositions of the cocoa beans after fermentation, cocoa liquors, and chocolates. The inoculated H. opuntiae strain was unable to prevail over background yeasts present in the fermenting cocoa pulp-bean mass. It led to under-fermented cocoa beans after four days of fermentation, which was however reflected in higher levels of polyphenols. Cocoa fermentation processes inoculated with a Saccharomyces cerevisiae strain enhanced flavour production during the fermentation and drying steps, which was reflected in richer and more reproducible aroma profiles of the cocoa liquors and chocolates. Sensory analysis of the cocoa liquors and chocolates further demonstrated that S. cerevisiae led to more acidic notes compared to spontaneous fermentation, as a result of an advanced fermentation degree. Finally, different VOC profiles were found in the cocoa beans throughout the whole chocolate production chain, depending on the fermentation process. Highlights: Hanseniaspora opuntiae is unable to prevail during SCI CFPs. Saccharomyces cerevisiae leads to an advanced fermentation degree. S. cerevisiae positively influences aroma profiles of cocoa liquors and chocolates. 1 H NMR spectroscopy allow to characterize cocoa of different fermentation degree. Underfermentation leads to higher levels of polyphenols.